2009
DOI: 10.1021/jp9073812
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of Nonfluorous CO2-Soluble Oligomers and Polymers

Abstract: Ab initio molecular modeling is used to design nonfluorous polymers that are potentially soluble in liquid CO2. We have used calculations to design three nonfluorous compounds meant to model the monomeric repeat units of polymers that exhibit multiple favorable binding sites for CO2. These compounds are methoxy isopropyl acetate, 2-methoxy ethoxy-propane, and 2-methoxy methoxy-propane. We have synthesized oligomers or polymers based on these small compounds and have tested their solubility in CO2. All three of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 44 publications
0
59
0
Order By: Relevance
“…There are also several factors that have been identified as having a negative impact on polymer solubility, including the presence of amine-functional groups and allyl polymers with a –CH 2 -spacer between the polymer backbone and the side chain or group [85,91]. These have since been used more as a set of guidelines as opposed to a set of hard-and-fast rules; poly(methyl acrylate) (PMA - Table 2, compound 22 ) has a greater degree of acetylation than poly(vinyl acetate) (PVAc - Table 2, compound 23 ) but has a much higher melting point and is insoluble in CO 2 [84]. …”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…There are also several factors that have been identified as having a negative impact on polymer solubility, including the presence of amine-functional groups and allyl polymers with a –CH 2 -spacer between the polymer backbone and the side chain or group [85,91]. These have since been used more as a set of guidelines as opposed to a set of hard-and-fast rules; poly(methyl acrylate) (PMA - Table 2, compound 22 ) has a greater degree of acetylation than poly(vinyl acetate) (PVAc - Table 2, compound 23 ) but has a much higher melting point and is insoluble in CO 2 [84]. …”
Section: Reviewmentioning
confidence: 99%
“…Beckman and Enick et al have a large body of both practical and theoretical work around polymer solubility in carbon dioxide [84]. The first reported use of ab initio modelling to design oxygenated hydrocarbon polymers for use in CO 2 was in 2009, where one oligomer and two polymers were synthesised and found to be soluble in CO 2 after ab initio predictions.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Current work is directed at applying these concepts to other dyes and investigating alternative non-fluorinated CO 2 -solublizing groups. 40 …”
Section: Methodsmentioning
confidence: 99%
“…The occurrence of multiple binding sites in an amorphous polymer with a low glass transition temperature is thought to be responsible for poly(vinyl acetate) displaying a greater degree of solubility in CO 2 than any other high molecular weight oxygenated hydrocarbon [26]. We recently designed novel oligomers that dissolved in CO 2 , including polyvinyl methoxymethylether and poly(3-acetoxyoxetane) [30] and also demonstrated that poly(1-O-(vinyloxy)ethyl-2,3,4,6-tetra-O-acetyl-b-D-glucopyranoside) (a polymer with pendant sugar acetate groups) and amorphous polylactic acid are CO 2 -soluble over a wide range of molecular weight [31]. Nevertheless, poly(vinyl acetate) (PVAc) remains the most CO 2 -soluble polymer composed solely of carbon, hydrogen and oxygen that has yet been identified.…”
Section: Introductionmentioning
confidence: 99%